Effect of High-Temperature Treatment of Pentasils on Their Acid and Catalytic Properties in Conversion of Straight-Run Naphthas; Russian Journal of Applied Chemistry; Vol. 74, iss. 11 - Erofeev V. I. Vladimir Ivanovich (Catalysis, 2001)
Title screen